After 2000 Stože landslide - Mikoš, Matjaž (Acta hydrotechnica, 2020)
The 2000 Stože Landslide with the consecutive wet debris flow with a volume close to 1 million m3 that hit the village of Log pod Mangartom in November 2000 had many consequences. It triggered vast efforts not only for the mitigation of the devastated area but also sparked many studies in several scientific disciplines. Various studies were performed in order to better understand this type of natural hazard and its consequences for the natural and built environment, and for society as a whole. After two decades since the disastrous event in 2000, this paper provides an aggregate survey different studies on this event performed by researchers and engineers, summarising this event%s impact on in-depth landslide research in Slovenia. The advancement in this field in Slovenia since 2000 is obvious.
Keywords: debris flows; drobirski tok; landslide research; landslides; naravna tveganja; naravne nesreče; natural disasters; natural risks; raziskovanje zemeljskih plazov; Stože; Stože landslide; zemeljski plazovi